EXPERIMENTAL AND NUMERICAL STUDY OF WATERMIST FIRE SUPPRESSION ENCLOSED POOL FIRE WITH FUEL VARIATION - Millah Urwatul Wutsqo, Hanna
The objective of this study is to address issues through the use of experiments and simulations in order to assess the efficacy of water mist in enclosed spaces with different types of fuels. A series of measurements were conducted to analyze the performance of water mist in extinguishing fires, considering factors such as extinguishing time, temperature reduction, and burning duration. To measure the average room temperature in the gas phase, a type K thermocouple with a diameter of ???????????????????????? was utilized. The water mist, with a median droplet size of ????????????????????????, was sprayed from the indoor ceiling. The simulation involved the use of Ethanol, Methanol and Gasoline RON 92 as fuels, and was conducted using the Fire Dynamics Simulator (FDS), an open source-based computational fluid dynamics model for fire flow. Uniform grid size of 1 cm throughout the computational domain. The results of the test indicate that the type of fuel used can impact the fire extinguishing capabilities of water mist in an enclosed space.